PERAN MANAJEMEN SUMBER DAYA MANUSIA (SDM) DALAM PENINGKATAN KINERJA ORGANISASI - Ajeng Kusuma Ningsih; Agus Wahyudi; Ivana Mei Yulianti; Alfito Yusuf Isa Sugihono (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Every organization must utilize all its resources, including human resources, HR is responsible for helping each employee maximize organizational performance. This research is useful for evaluating the significance of human resource management in improving company performance. This research adopts a qualitative approach with an interactive analysis model developed by Miles and Huberman. Repeated and interactive analysis is carried out until the data becomes saturated, and involves reduction, delivery, and drawing conclusions. Studies show that management and business performance are better with human resource management (HR).